All‐Solid‐State Vertical Three‐Terminal N‐Type Organic Synaptic Devices for Neuromorphic Computing. (20th February 2022) - Xie, Zhichao; Zhuge, Chenyu; Zhao, Yanfei; Xiao, Wei; Fu, Yujun; Yang, Dongliang; Zhang, Shunpeng; Li, Yingtao; Wang, Qi; Wang, Yazhou; Yue, Wan; McCulloch, Iain; et al.
Abstract: Artificial synaptic devices are the basic composition units for neuromorphic computing processors that realize massive parallel computing. However, the n‐type organic transistors have failed to achieve good performance as an artificial synaptic device for neuromorphic computing until now. Here, a vertical three‐terminal n‐type organic artificial synapse (TNOAS) using a lithium ion‐based organic dielectric and the n‐type donor–acceptor (D–A) conjugated polymer‐naphthalene‐1, 4, 5, 8‐tetracarboxylic‐diimide‐thiophene‐vinyl‐thiophene (NDI‐gTVT) as the channel is proposed. The TNOAS achieves nonvolatile conductance modulation with high current density operation (≈10 KA cm −2 ) at low voltage and mimics the basic functions of biological synapses, such as long‐term synaptic plasticity and paired‐pulse facilitation. The minimum energy consumption of a response event triggered by a single action potential is 6.16 pJ, which can be comparable with p‐type counterparts. Moreover, simulation using handwritten digital datasets exhibit a high recognition accuracy of 94%. Abstract : A novel n‐type organic synaptic device mimics the basic synaptic functions in the high current density working states controlled by low voltage. This is the first time that n‐type organic copolymer is used as the active layer of artificial neural devices to realize high electrical performance.